1991
DOI: 10.1172/jci115106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that tumor necrosis factor plays a pathogenetic role in the paraneoplastic syndromes of cachexia, hypercalcemia, and leukocytosis in a human tumor in nude mice.

Abstract: Recently, we have established a human squamous cell carcinoma of the maxilla (called MH-85) associated with hypercalcemia, leukocytosis, and cachexia in culture. MH-85 tumor cells caused the same paraneoplastic syndromes in tumor-bearing nude mice. We found that there was a sixfold increase in splenic size in MH-85 tumor-bearing mice. This increase paralleled tumor growth and was reversed by surgical removal of the tumor. Splenectomy in nude mice 1 wk before or 6 wk after tumor inoculation resulted in a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
1
3

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 52 publications
0
50
1
3
Order By: Relevance
“…Lung carcinoma has been known to have a predilection for spreading to bone. 10 Recent studies suggest that PTH-rP plays a critical role in tumor invasion and distant metastasis 22,23 and facilitates dissemination of breast and prostate carcinoma to bone. 6,24 -26 These previous observations led us to determine the relation between serum levels of PTH-rP and the development of bone metastases in lung carcinoma patients with TIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung carcinoma has been known to have a predilection for spreading to bone. 10 Recent studies suggest that PTH-rP plays a critical role in tumor invasion and distant metastasis 22,23 and facilitates dissemination of breast and prostate carcinoma to bone. 6,24 -26 These previous observations led us to determine the relation between serum levels of PTH-rP and the development of bone metastases in lung carcinoma patients with TIH.…”
Section: Discussionmentioning
confidence: 99%
“…We specifically examined the relation between serum levels of PTH-rP and bone metastases because lung carcinoma has a strong predilection for spreading to bone 10 and PTH-rP is implicated in bone metastases in malignancies such as breast carcinoma. 5 Our data confirm that PTH-rP is elevated in lung carcinoma patients with TIH.…”
mentioning
confidence: 99%
“…Cachexia is known to be caused by mediators produced by tumours or by the host as a result of tumour-host interaction. Previously, various factors have been proposed as cachexia mediators, such as tumour necrosis factor alpha (TNF-α) (Oliff et al, 1987;Tracey et al, 1988;Stovroff et al, 1988;Yoneda et al, 1991), interferon gamma (IFN-γ) (Matthys et al, 1991a(Matthys et al, , 1991b, interleukin (IL)-1α (Moldawer et al, 1987;Gelin et al, 1991), leukaemia inhibitory factor (LIF) (Mori et al, 1991) and IL-6 (Yoneda et al, 1993;Tamura et al, 1995). Fujimoto-Ouchi et al (1995) and Strassmann et al (1992a) reported that anti-IL-6 antibody suppressed the progressive body weight loss and other disorders associated with cachexia in mice bearing colon 26.…”
mentioning
confidence: 99%
“…8,34) However, it has been reported that several inflammatory cytokines, which are produced by host immune cells or tumor cells themselves, could influence the production of G-CSF and PTHrP during the course of malignant disease. 28) Indeed, Rizzoli et al have shown that PMA, IL-6 and TNF-α induced an increase in PTHrP production by a human lung squamous cell carcinoma line, which was associated with elevated levels of PTHrP mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,28,29) The production of G-CSF and PTHrP by cancer cells is thought to be responsible for these paraneoplastic syndromes. However, the mechanism of simultaneous and unrestricted production of G-CSF and PTHrP by cancer cells is not well delineated.…”
Section: Discussionmentioning
confidence: 99%